Development and evaluation of ibuprofen-loaded chitosan nanoparticles for pulmonary therapy - Olvera Rodríguez, I.; Mora-Muñoz, J. M.; Pérez, V.; Campos-Guillén, J.; Gallegos-Reyes, M. A.; García-Solís, P.; Álvarez López, A.; Vallejo Becerra, V.; Rodríguez-Morales, J. A.; Rodríguez-Méndez, A. J.; Guzmán Martínez, C. (Frontiers in Nanotechnology, 2024)
Lung injuries are increasingly prevalent due to various diseases causing alveolar damage, potentially leading to respiratory disorders. This study employed an incubation method to develop nano-encapsulated ibuprofen within a chitosan matrix for targeted pulmonary therapy. The encapsulation was successful without altering the molecular structure of chitosan, and a 500 mg dose was identified as optimal through lung tissue cell viability and histological analysis. The controlled release mechanism of this formulation ensures targeted delivery to the lungs, reducing inflammation and promoting alveolar regeneration. This approach highlights the importance of dose optimization and presents a promising strategy to enhance the efficacy and safety of pulmonary treatments.